Answer:
t = D/r
Step-by-step explanation:
you rearrange the equation so that is the subject. when you bring something over the equal sign, it reverses the function so D = r×t becomes t = D/r
f(3) is equal to -101.
<u>Step-by-step explanation</u>:
- The sequence is followed by f(0)=4
- The given expression is f(n+1)= -3f(n)+1
Put n=0,
f(0+1)= -3f(0)+1
f(1)= -3(4)+1
f(1)= -12+1 = -11
Put n=1,
f(1+1)= -3f(1)+1
f(2)= -3(-11)+1
f(2)= 33+1 = 34
Put n=2,
f(2+1)= -3f(2)+1
f(3)= -3(34)+1
f(3)= -102+1
f(3)= -101
Answer:
4
<h3>When u have a bank account and are 8 dollars below proficiency and you add 12 dollars to your bank account</h3>
Step-by-step explanation:
add 12 to -8
4
Answer:
isnt it by the Y-intercept?
Step-by-step explanation: